Ammonia recovery from organic nitrogen in synthetic dairy manure with a microbial fuel cell. (June 2023) - Burns, McKenzie; Qin, Mohan
Abstract: Increasing pressures on the animal and cropland agriculture sectors have led to the realization of problems with animal waste management and ammonia-based fertilizer supply. Bioelectrochemical systems (BES) are a new-age technology that offer a way to address these problems. Microbial fuel cells (MFCs), one type of BES, are traditionally used for electricity generation from microbial degradation of organic matters, but can also be used to recover nutrients from wastes simultaneous with treatment. This research investigated an MFC for ammonia recovery from the organic nitrogen (orgN) fraction of synthetic dairy manure, using the simple amino acid glycine as the orgN source. We used five different synthetic manure compositions to determine their effects on MFC performance, and found minimal sacrifices in performance under orgN conditions when compared to the base condition without orgN. The MFC achieved greater than 90% COD removal in all orgN conditions. Nitrogen (N) removal efficiencies of between 40% and 60% were achieved in orgN conditions, indicating that organic nitrogen can be used as the substrate for ammonia mineralization and further recovery as fertilizer. In addition, we found the MFC was largely populated by electrogenic organisms from the phyla Bacteroidota, Firmicutes, Proteobacteria, and Halobacterota, with organisms in both Bacteroidota and Firmicutes capable of N mineralization present. Lastly, we found that in conditions where orgN is scarce and the only N source provided, microbes preferentially degraded organic matter from other dead organisms, especially as an N source. This increases the concentration of N in the MFC system and introduces important operational constraints for MFCs operated for ammonia recovery from orgN. Graphical abstract: Image 1 Highlights: Ammonia recovery is a competitive application for microbial fuel cells. Microbial fuel cells can achieve N mineralization to recover ammonia from organic N. Bacteriodota and Firmicutes microbes may contribute to current & N mineralization. Microbes preferentially degrade necromass when organic N is limiting.